Development of the composition of a lubricant for injection under pressure with high sedimentation stability - A. A. Pivovarchyk; A. M. Mikhaltsov; Ya. I. Tsishkova (Литьë и металлургия)
The article describes the requirements for the lubricant used in injection molding of non-ferrous alloys. A methodology for conducting research to determine the sedimentation stability of a prepared lubricant is presented, as well as the results of a study of the sedimentation stability of a lubricant used in non-ferrous alloy die casting. It was established that in order to significantly increase the sedimentation stability of the compositions of lubricants for casting silumin based on the selected components, it is necessary to pre-heat the initial components to a temperature of at least 80 °C and mix them at a rotational speed of the dispersant blades of at least 6000 min–1. The optimal mode of lubrication with high sedimentation stability (more than 200 days) is observed at the following temperature and time indicators: the temperature of the heating of the starting components is at least 90 °C, the mixing time is 5 minutes, and the mixing frequency is 18000 min–1.